Interventional Spine Procedures for Management of Chronic Low Back Pain—A Primer - Iannuccilli, Jason D.; Prince, Ethan A.; Soares, Gregory M. (Seminars in Interventional Radiology, 2013)
Chronic low back pain is a common clinical condition. Percutaneous fluoroscopic-guided interventions are safe and effective procedures for the management of chronic low back pain, which can be performed in an outpatient setting. Interventional radiologists already possess the technical skills necessary to perform these interventions effectively so that they may be incorporated into a busy outpatient practice. This article provides a basic approach to the evaluation of patients with low back pain, as well as a review of techniques used to perform the most common interventions using fluoroscopic guidance.
Keywords: back pain injections; spine intervention; epidural steroid injection; facet block; medial branch block; interventional radiology